Politik Hukum Penguatan Partisipasi Perempuan Dalam Pembangunan Desa Berbasis Keadilan Gender - Sapto Budoyo; Marzellina Hardiyanti (Administrative Law and Governance Journal, 2021)
Abstract Village Development is one of the national developments, wich is regulated in the Law Number 6 of 2014 concerning Villages. In village development, community participation is needed, including women's participation, which is currently still minimal in providing aspirations for village development. Therefore, it is necessary to strengthen women's participation in village development in order to accommodate policies related to women so that they are able to realize gender equitable village development. The basis for protecting women and strengthening women's rights in national development is the existence of Law Number 7 of 1984 concerning the Elimination of All Forms of Discrimination against Women. In writing this paper using legal research methods with a literature approach to obtain accurate data. The politics of law regarding strengthening women's participation seeks to accommodate women's aspirations in providing their participation for the protection of women at the regional or village level. Keywords: Women's Participatio, Village Development, and Gender Equitable.  Abstrak Pembangunan Desa merupakan salah satu pembangunan nasional yang diatur dalam Undang-Undang Nomor 6 Tahun 2014 tentang Desa. Dalam pembangunan desa diperlukan partisipasi masyarakat, termasuk partisipasi perempuan yang saat ini masih minim dalam memberikan aspirasi untuk pembangunan desa. Oleh karena itu, diperlukan penguatan partisipasi perempuan dalam pembangunan desa agar dapat mengakomodasi kebijakan terkait perempuan sehingga mampu mewujudkan pembangunan desa yang berkeadilan gender. Landasan perlindungan perempuan dan penguatan hak-hak perempuan dalam pembangunan nasional adalah dengan adanya Undang-Undang Nomor 7 Tahun 1984 tentang Penghapusan Segala Bentuk Diskriminasi terhadap Perempuan. Dalam penulisan skripsi ini menggunakan metode penelitian hukum dengan pendekatan kepustakaan untuk memperoleh data yang akurat. Politik hukum tentang penguatan partisipasi perempuan berupaya mengakomodir aspirasi perempuan dalam memberikan partisipasinya untuk perlindungan perempuan di tingkat daerah atau desa. Kata Kunci : Partisipasi Perempuan, Pembangunan Desa, dan Keadilan Gender.